O papel dos professores na construção da autonomia moral dos alunos: como pensam e o que fazem - Montanha, Lilian Thiago [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The main objective of this study was to understand - through interviews and observations - what teachers think and what they do of the Fundamental education with regard to ethics and moral formation of students. The process of teaching and learning, targeted through formal schooling, involves some important dimensions such as technical, human and political. It is a fact that the school has been working the technical dimension and content, somehow, over the years. However, the political and human dimensions do not appear so clearly in the educational process. A school divided into series, fragmented and isolated from everyday life permeates currently the schools. Thus the relevance of this research whose method adopted was the ethnographic, by allowing closer relationship with the social group, facilitating an overall understanding of the data. The study included teachers of Elementary School I and II of two public elementary schools in the city of Assis, within the State of São Paulo. By observing the daily life and the dynamics between teachers and students has been facilitated the interpretation of data and enabled the verification of the methods used by teachers in their practice by offering to the speech captured in an interview a more vivified feature. It is noteworthy that moral development is the result of an ongoing process that occurs through the relationships established between individuals in different spaces that they inhabit and, in the improvement of this process, the school and the teachers play a fundamental role. For the analysis of the data was followed a three-stage procedure: first, were listed core-base of the questions proposed to teachers; in the next step, between observations, it was highlighted what is called scenes in order to elucidate the most significant moments of this phase; and finally we proceeded to the verification of which was brought in common or unique by...

O objetivo principal deste trabalho consistiu em compreender - valendo-se de entrevistas e de observações - o que pensam e o que fazem professores do Ensino Fundamental no que se refere à formação ética e moral dos educandos. O processo de ensino e aprendizagem, pensado por meio da escolarização formal, envolve algumas dimensões importantes como a técnica, a humana e a política. É fato que a escola vem trabalhando a dimensão técnica e de conteúdos, de alguma forma, ao longo dos anos. No entanto, as dimensões políticas e humanas não aparecem tão claramente no processo pedagógico. Um ensino dividido em séries, fragmentado, e isolado do cotidiano permeia, atualmente, as escolas. Daí a pertinência desta pesquisa cujo método adotado foi o da investigação do tipo etnográfico, por permitir aproximação maior com o grupo social, facilitando uma compreensão global dos dados. Participaram deste estudo professores dos Anos Iniciais e Finais do Ensino Fundamental de duas escolas públicas da cidade de Assis, interior do estado de São Paulo. Observar o cotidiano e a dinâmica dos professores com os alunos facilitou a interpretação dos dados e possibilitou a verificação dos métodos utilizados pelos professores em sua prática, oferecendo à fala captada em entrevista um caráter mais vivificado. Cabe ressaltar, que o desenvolvimento moral é resultante de um processo contínuo que ocorre por meio das relações estabelecidas entre os indivíduos nos diferentes espaços que habitam e, no decorrer desse processo, a escola e os professores possuem papel fundamental. Para a análise dos dados seguiu-se um procedimento de três fases: inicialmente, foram elencados núcleos-base das questões propostas aos docentes; na sequência, entre as observações, destacou-se o que se denominou de cenas, a fim de elucidar os momentos mais significativos desta fase; e, finalmente, procedeu-se...
Keywords: Ética; Professores de ensino fundamental; Psicologia do desenvolvimento; Desenvolvimento moral; Ethics